De nasleep van Somalië, Rwanda en Srebrenica: overeenkomsten en verschillen - Brocades Zaalberg, Thijs (BMGN - Low Countries Historical Review, 2010)
Klep, Christ, Somalië, Rwanda, Srebrenica. De nasleep van drie ontspoorde vredesmissies (Dissertatie Utrecht 2008; Amsterdam: Boom, 2008, 385 blz., ISBN 978 90 8506 668 2) The Aftermath of Somalia, Rwanda and Srebrenica: Parallels and Differences Christ Klep has written an impressive and highly accessible thesis on the aftermath of three unsuccessful peace operations. By using a bold comparative approach and an ambitious tone of enquiry he places the traumatic Dutch Srebrenica experience in the context of two broadly similar processes of finger-pointing and evading responsibility in Canada and Belgium following their respective interventions in Somalia and Rwanda. He thus exposes many fascinating parallels, yet the historian Klep pays little attention to the differences between his case studies. This is regrettable, as this would have strengthened rather than weakened his otherwise compelling argument. The Somali case in particular differs from ‘Srebrenica’ and ‘Rwanda’, since the murders perpetrated by Canadian soldiers – horrific as they may have been – and the subsequent cover-up in no way constituted a defining moment in the collapsing international mission as a whole. Unlike the genocides in Rwanda and Srebrenica the death of the two Somalis was the result of a purely national Canadian failure, which helps explain why the Somalia Inquiry could identify guilty compatriots far more decisively than, for example, the Netherlands Institute for War Documentation (NIOD) in its Srebrenica report. This review is part of the discussion forum ’Somalië, Rwanda, Srebrenica’ (Christ Klep).